Developing environmentally responsibly investment in Kazakhstan - Kizimbayeva Azhar; Zhumanova Bekarshyn; Yessymkhanova Zeinegul; Dauletkhanova Zhanar; Mukhamejanova Aigul (E3S Web of Conferences, 2023)
The article examines the development and formation of green finance in Kazakhstan. It is noted that green finance is now becoming The article defines the essence of responsible investment within the framework of the concept of ESG investment which takes into account the unity of environmental, social and corporate governance factors; an analysis of the status and development of responsible investment factors and corporate governance factors; the analysis of the status and development of responsible investments in economically developed countries; the possibilities of formation of ecosystem of financial support of ecologically responsible investments were estimated ecosystem of financial support for environmentally responsible investments in Kazakhstan; the following factors constraining and stimulating investments in “green” economy projects were identified, the measures of state support for environmentally responsible investment in the country have also been proposed. Investments in the country; and the measures proposed by the government to support the development of environmentally responsible investments in the country. Systematisation and refinement of scientific and theoretical approaches to defining The essence and economic content of environmentally responsible investment in the framework of The concept of ESG-investments and study of the possibility of their implementation in the practice of Kazakhstan.